A Müllerian cyst in a male adolescent: a case report and literature review. Issue 5 (May 2021) - He, Jun; Tang, Kaifa
Müllerian duct cyst is a congenital anomaly that originates from an abnormality in the degradation of the Müllerian system and remnants of the Müllerian duct. Müllerian cyst is rarely reported in male adolescents younger than 18 years of age. In this case report, a 17-year-old male adolescent presented with a scrotal mass of 6 years' duration. Ultrasonography and computed tomography revealed a left scrotal mass, and the patient underwent open surgical resection of the cyst. Histologically, the cyst consisted of tall columnar cells and was consistent with a Müllerian duct cyst. We discuss the presentation and imaging findings in this case, drawing attention to the diagnosis and treatment.